Mizhuo Guanchangye enema delays the decline of renal function in rats with chronic kidney disease by intervening in the TLR4/MyD88/NF-κB pathway - Li, Han; Xu, Peng; Zhang, Xiaomei; Ye, Naijing; Xu, Fang; Liang, Bo (Frontiers in Medicine, 2024)
Background: Chronic kidney disease (CKD) is a prevalent chronic condition that poses a significant threat to human health. There is a close connection between the gut and kidneys, jointly influencing the onset and progression of CKD through the "gut-kidney axis." Traditional Chinese medicine has shown potential in CKD treatment, but the specific mechanisms require further investigation.Objectives: This study aims to explore the protective effects of Mizhuo Enema (MZGCY) on kidney function in CKD rats by regulating the TLR4/MyD88/NF-κB signaling pathway.Methods: The researcher employed a CKD rat model, which was divided into four groups: Control, Model, half-dose Mizhuo Guanchangye (1/2 MZGCY), and full-dose Mizhuo Guanchangye (MZGCY). Post enema administration, assessments were conducted on kidney function indicators, which included blood urea nitrogen (BUN), serum creatinine (SCR), and 24-hour urinary protein.Additionally, measurements were taken for intestinal toxic substances such as indoxyl sulfate (IS) and lipopolysaccharide (LPS), as well as inflammatory factors interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). Examinations of pathological changes in both the intestines and kidneys were also performed. During this process, immunofluorescence was utilized to detect the expression levels of proteins toll-like receptor 4 (TLR4), myeloid differentiation primary response 88 (MyD88), and nuclear factor kappa B (NF-κB) in the intestinal tissues. Results: It was found that after enema treatment, the BUN, SCR, and 24-hour urinary protein levels in the MZGCY and 1/2 MZGCY groups significantly decreased, indicating notable improvement in kidney function. Compared to the model group, the IS, LPS, IL-6, and TNF-α levels in the MZGCY and 1/2 MZGCY groups were significantly reduced. Immunofluorescence showed a marked decrease in the expression of TLR4, MyD88, and NF-κB proteins in the intestines of the MZGCY group.Conclusion: MZGCY significantly reduces the levels of intestinal toxins and inflammatory factors in the serum of CKD rats by interfering with the TLR4/MyD88/NF-κB signaling pathway, thereby improving intestinal and renal pathological changes and delaying CKD progression. This study demonstrates that MZGCY has significant renal protective effects, providing a new potential approach for CKD treatment.